(untitled) (Research, Society and Development, 2021)
Sickle cell disease (SCD) is a hemoglobinopathy of predominance of hemoglobin S in red blood cells, of a genetic character. The objective of this study was to describe the epidemiological and clinical profile of 64 users with DF from the Municipal Reference Center for people with DF in the municipality of Feira de Santana / BA, from November 2016 to March 2017. The present study was submitted and approved by a research ethics committee. The predominance was female, race / color was brown / black, education less than 8 years of study, income less than or equal to a minimum wage and without occupation. As for clinical conditions, most had a medical diagnosis of sickle cell anemia and the disease was discovered through the heel prick test. Although the majority did not have comorbidities, a high number of participants presented some type of complication related to the disease, with more frequent pain attacks, pneumonia, acute chest syndrome and splenic sequestration. The results presented can be used by the service as an instrument to outline a care plan for this population according to the epidemiological and clinical profile of users, as well as reinforcing the importance of strategies such as health education, to minimize the occurrence of complications.